DESAIN KARAKTER UTAMA WEB KOMIK RADEN SAWUNGGALING SEBAGAI MEDIA PENGENALAN TOKOH LOKAL BERSEJARAH UNTUK REMAJA USIA 17-21 TAHUN - I Putu Rayga Ondias Putra; Alfian Candra Ayuswantana; Masnuna, Masnuna (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The declining awareness among youth about local historical figures such as Raden Sawunggaling inspired the creation of this web comic. Aimed at teenagers aged 17–21, this project seeks to reintroduce local history through a visually engaging and interactive medium. The comic features a flowing narrative, semi-realistic illustrations, and strong elements of East Javanese culture. Its design was informed by qualitative and quantitative research to align with the preferences of the target audience. The web comic format was chosen for its accessibility, cost-efficiency, and relevance to the digital habits of today’s youth. This medium is expected to reignite interest in local history while serving as a creative and educational approach to cultural preservation.